1994
DOI: 10.1056/nejm199404283301703
|View full text |Cite
|
Sign up to set email alerts
|

Infusions of Donor Leukocytes to Treat Epstein-Barr Virus-Associated Lymphoproliferative Disorders after Allogeneic Bone Marrow Transplantation

Abstract: In a small number of patients, infusions of unirradiated donor leukocytes were an effective treatment for EBV-associated lymphoproliferative disease that arose after allogeneic bone marrow transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
531
1
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,023 publications
(541 citation statements)
references
References 30 publications
4
531
1
4
Order By: Relevance
“…6,7 To the best of our knowledge, this is the first report of DLT for the treatment of EB-LPD in the CNS. It was not clear whether the infused lymphocytes had penetrated into the CNS.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…6,7 To the best of our knowledge, this is the first report of DLT for the treatment of EB-LPD in the CNS. It was not clear whether the infused lymphocytes had penetrated into the CNS.…”
Section: Discussionmentioning
confidence: 84%
“…6,7 We report the case of a Japanese woman, who developed EBV-LPD of the right cerebrum following allogeneic BMT and who was then treated with DLT.…”
Section: Discussionmentioning
confidence: 99%
“…Papadopolous et al [28] found that infusion of donor leucocytes was effective in patients with EBV-associated lymphoproliferative disease who had undergone allogeneic bone marrow transplantation. Precursors of anti-EBV CTL in the infused leucocytes appeared to be expanded in vivo to control EBV-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 For this reason, the EBV-directed CTL response has been carefully investigated after allogeneic BMT, where up to 30% of the recipients of allografts from mismatched or matched unrelated donors may develop EBV lymphoma. 20,21 The aims of our study were: (1) to determine whether a specific EBV-directed cytolytic activity exists after PBSCT; (2) to characterize this CTL response; and (3) to analyze qualitatively this CTL response in some patients with lymphoid malignancies early vs late after PBSCT. By these means we wished to determine whether the assessment of the EBV-specific CTL response can be used as a surrogate marker for the reconstitution of the antigen-specific T cell response after PBSCT.…”
mentioning
confidence: 99%